The classic foundations of capital accumulation in Piketty - Tobón, Alexander; Ríos, Yohan S. (Sociedad y Economía, 2020)
The aim of this paper is to propose a model that permits to analyze the theoretical scheme of the capital accumulation in Piketty, from an adaptation of the classic model propsed by Bidard and Klimovsky (2006). The relation between both theoretical conceptions operates through the equation of Pasinetti, which facilitates the distinction between the situations of imbalance and balance. This way, the model identifies the conditions that explain the gap between the rate of benefit and the rate of growth of the national income.